GOVERNANÇA PÚBLICA NOS PLANOS DE CONTINGÊNCIA DE DEFESA CIVIL: DESENVOLVIMENTO E APLICAÇÃO DE ÍNDICE AVALIATIVO (Interdisciplinary Studies Journal, 2024)
This article aims to measure the repercussion of the principles of public governance on the disaster management tools provided by the National Civil Defense System, placing emphasis on the structuring of the Civil Defense and Protection Contingency Plans (PCPDC), foreseen in the Metropolitan Region of Curitiba (RMC ). It is understood that good governance practices ensure adequate mechanisms to provide a balance of power between the community and the public entity responsible for public loss protection policies. From these points, the question is: “How to measure the effectiveness of public governance principles in the structure of PCPDC in municipalities based on the development of an evaluation index?” The objective is to develop an index to evaluate the principles of public governance in civil defense (IGovDC) linked to disaster management. Bibliographic and documentary research with a qualitative and quantitative approach is used to structure and apply the proposed index. As a result, the municipalities orbit in the “medium” range in the range proposed by the index, showing that the PCPDC satisfactorily meet the stipulated criteria. However, there are reservations in how much municipal managers have anchored themselves in the standardized Online Contingency Plan (PCO) model made available by the state agency, restricting themselves to the basics to comply with the imposed legal obligation.
Keywords: Disasters; Public Governance; Civil defense